The Effectiveness of Knee Exercise to Pain Intensity in Elderly Patients of Knee Osteoarthritis - Priyanto, Agus; Abdillah, Alvin; Sadiyah , Halimatus (Kirana Publisher (KNPub), 2022)
Pain is a physiological reaction due to a protective reaction to avoid stimuli that harm the body. Based on the results of the preliminary study, it was found that there were still many patients who experienced pain in the elderly with osteoarthritis . The purpose of this study was to analyze the effect of knee exercise therapy on reducing the level of knee osteoarthritis pain intensity . The research design is a quasy experiment. The population is 184 elderly with a sample of 32 respondents using simple random sampling . The independent variable is knee exercise therapy and the dependent variable is pain intensity in the elderly who suffer from osteoarthritis . The research instrument is the pain scale observation sheet. This study uses an observation sheet . Data analysis used the Wilcoxon test and the Mann Whitney test .Based on statistical test results Wilcoxon obtained p value (0.001) < α (0.05) meaning that there is a difference in pain intensity after being given knee exercise therapy, Wilcoxon statistical test results obtained p value (0.122) < α (0.05) meaning there is a difference in pain intensity after being given deep breathing relaxation therapy and the results Mann Whitney statistical test obtained p value (0.003) <α (0.05) meaning that there is a difference in pain scale after being given knee exercise therapy and deep breathing relaxation. Knee exercise therapy is effective in reducing pain intensity in patients with osteoarthritis. Researchers hope that health workers will maintain and continue providing health education on knee exercise therapy in non-pharmacological management of the elderly with osteoarthritis.